Eurasian integration: from post-Soviet to new regional projects - Turarbekova, Roza M. (Journal of the Belarusian State University. International Relations, 2020)
The article considers the problem of Eurasian integration as a contradictory process that has gone from disintegration of a single political and economic union to the beginning of the formation of a new regional organization of the Eurasian Economic Union (EEU). The peculiarity of considering the problem is the combination of two research approaches: historical institutionalism and context analysis. As a result, the author concludes that the EEU member states are not very flexible in creating strong supranational bodies due to the specific character of their own political systems. On the other hand, the real economic interests of all EEU countries and Russia’s geopolitical motives are centripetal factors.
Keywords: Belarus; Russia; Kazakhstan; foreign policy; Eurasian integration; institutional design; regional projects; CIS; EEU; Belt and Road initiative